Earth-abundant Electrocatalytic Materials for the Hydrogen Economy - Bird, Matthew A. (2023)
The production of hydrogen through sustainable methods is key in the development of a hydrogen economy to help decarbonise society. One such route is through the electrolysis of water. This will require novel electrocatalysts to overcome the sluggish kinetics of the oxygen evolution reaction and to avoid the expensive and rare materials, such as platinum and iridium oxides, currently used to electrocatalyse this reaction. In the testing of electrocatalysts, Pt and Au are often as counter electrode materials. This thesis shows their use is unsuitable due to the dissolution of the metals when used in the conditions typical of electrocatalytic testing. The dissolved metals diffuse from the counter electrode to the working electrode where they can then deposit. This artificially enhances the measured electrocatalytic activity. The use of a Nafion membrane to prevent the crossover of these contaminants is found to be ineffective. A carbon-based counter electrode separated from the working electrode using a membrane or frit is shown to be the best set-up. This thesis sets out to explore three strategies that can be used in the design of novel electrocatalysts. Synergistic interactions between Co3O4 and single-walled nanotubes (SWNT) are explored through encapsulating the oxide inside the tubes. This interaction leads to an enhancement in the mass activity of the electrocatalyst system towards the oxygen evolution reaction (OER) by altering the surface chemistry of the SWNT. Second, morphological control is examined by modifying titanate microspheres with a sodium titanate layer. This is shown to maintain the underlying structure whilst increasing the specificity of the electrocatalyst towards the 2x2e oxygen reduction reaction (ORR). Heat-treatment then increases the surface area without impacting this specificity. The mechanism of the ORR can also be controlled through doping BaTiO3 with La such that the structure changes from hexagonal to tetragonal. This third design strategy is further explored by increasing the amount of Pr doped into (Ba0.5Sr0.5)1−xPrxCo0.8Fe0.2O3−δ. This decreases how cubic the structure is, as evidenced through XRD, and is correlated to decreasing OER activity.